Is Blended Learning Effective in Developing Critical Thinking Skills? : A Meta-Analysis Study - Aris Martiana; Siti Irene Astuti Dwiningrum; Suranto Aw (Universitas Negeri Yogyakarta, 2025)
Increasingly sophisticated and modern technology provides convenience to humans in various fields. Many benefits can be received, although there is still a side to the problem regarding technological developments. This also happens in the field of Education which has utilized technology today. Blended learning with a blended method is an innovation in Education that is associated with the critical thinking ability of school students at the primary, secondary and higher education levels. This research is quantitative with a meta-analysis design using 24 ar-ticle studies with predetermined criteria with secondary data sources sourced from Google Scholar, Research Gate and Science Direct with the years 2014, 2018, 2019, 2020, 2021 and 2022. The article is determined using mean aggregates. The existence of coding, according to the purpose, of this article focused on N, M, and SD data. The data processing is assisted by Microsoft Excel and JASP software. This is done to estimate aggregates, project forest plots, test heterogeneity, and investigate publication bias. The analysis found that there is accuracy in using a random effect model aggregate with a high heterogeneity effect size and no prob-lems in publication, so following the research objective the blended learning model is effective in developing critical thinking skills in learning so that technology in education has a positive impactKeywords: Blended learning, critical thinking, meta-analysis, effective